Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3+3^2+3^3+...+3^{2012}\)
\(=\left(3+3^2+3^3+3^4\right)+...+\left(3^{2009}+3^{2010}+3^{2011}+3^{2012}\right)\)
\(=3\left(1+3+3^2+3^3\right)+...+3^{2009}\left(1+3+3^2+3^3\right)\)
\(=40\left(3+...+3^{2009}\right)⋮40\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : A = 30 + 31 + 32 + 33 + .... + 350
=> 3A = 31 + 32 + 33 + 34 + ... + 351
Khi đó 3A - A = (31 + 32 + 33 + 34 + ... + 351) - (30 + 31 + 32 + 33 + .... + 350)
=> 2A = 351 - 30
=> A = \(\frac{3^{51}-1}{2}\)
Khi đó A = \(\frac{3^{51}-1}{2}=\frac{3^3.3^{48}-1}{2}=\frac{27.\left(3^4\right)^{12}-1}{2}=\frac{27.\left(...1\right)^{12}-1}{2}\)
\(=\frac{\left(...7\right)-1}{2}=\frac{\left(...6\right)}{2}=\left(...3\right)\)
Vậy A tận cùng là 3
![](https://rs.olm.vn/images/avt/0.png?1311)
`A=1+2^2 +2^3 +...+2^10`
`2A=2+2^3 +2^4 +...+2^11`
`A=2+2^3 +2^4 +...+2^11 -1-2^2 -2^3 -...-2^10`
`A=2+2^11 -1-2^2`
`A=2+2048-1-4`
`A=2045`
Đặt: \(A=1+2^2+2^3+...+2^{10}\)
\(\Rightarrow2A=2\cdot\left(1+2^2+2^3+...+2^{10}\right)\)
\(\Rightarrow2A=2+2^3+2^4+...+2^{11}\)
\(\Rightarrow2A-A=\left(2+2^3+2^4+...+2^{11}\right)-\left(1+2^2+2^3+...+2^{10}\right)\)
\(\Rightarrow A=2+2^3+2^4+...+2^{11}-1-2^2-2^3-...-2^{10}\)
\(\Rightarrow A=\left(2^3-2^3\right)+\left(2^4-2^4\right)+...+\left(2^{10}-2^{10}\right)+\left(2+2^{11}-1-2^2\right)\)
\(\Rightarrow A=0+0+0+...+2+2^{11}-1-2^2\)
\(\Rightarrow A=2+2^{11}-1-4\)
\(\Rightarrow A=2^{11}-3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(B=\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+\frac{1}{5^2}+\frac{1}{6^2}+\frac{1}{7^2}+\frac{1}{8^2}\)
\(\Rightarrow B=\frac{1}{2^2}+...+\frac{1}{8^2}< \frac{1}{1.2}+...+\frac{1}{7.8}\)
\(\Rightarrow\frac{1}{2^2}+...+\frac{1}{8^2}< 1-\frac{1}{2}+...+\frac{1}{7}-\frac{1}{8}\)
\(\Rightarrow\frac{1}{2^2}+...+\frac{1}{8^2}< 1-\frac{1}{8}\)
\(\Rightarrow\frac{1}{2^2}+...+\frac{1}{8^2}< \frac{7}{8}< 1\)
\(\Rightarrow B< 1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. ( 2x + 1 )2 = 49
<=> ( 2x + 1 )2 = 72
<=> 2x + 1 = 7
<=> x = 3
b. ( 2x - 1 )4 = 81
<=> ( 2x - 1 )4 = 34
<=> 2x - 1 = 3
<=> x = 2
c. ( x + 1 )3 = 2x3
<=> x + 1 = 2x
<=> x = 1
d. ( 2x + 1 )3 = 3x3
<=> 2x + 1 = 3x
<=> x = 1
( 2x + 1 )2 = 49
<=> ( 2x + 1 )2 = ( ±7 )2
<=> \(\orbr{\begin{cases}2x+1=7\\2x+1=-7\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=-4\end{cases}}\)
( 2x - 1 )4 = 81
<=> ( 2x - 1 )4 = ( ±3 )4
<=> \(\orbr{\begin{cases}2x-1=3\\2x-1=-3\end{cases}}\Rightarrow\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
( x + 1 )3 = ( 2x )3
<=> x + 1 = 2x
<=> x - 2x = -1
<=> -x = -1
<=> x = 1
( 2x + 1 )3 = ( 3x )3
<=> 2x + 1 = 3x
<=> 2x - 3x = -1
<=> -x = -1
<=> x = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
A<1-1/2+1/2-1/3+...+1/8-1/9=1-1/9=8/9 A>1/2-1/3+1/3-1/4+...+1/9-1/10=1/2-1/10=2/5 =>2/5<A<8/9